Understanding tree-growing decisions of smallholder farmers in Claveria, Northern Mindanao, The Philippines - Predo, Canesio D.; Francisco, Herminia A. (2006)
The study was conducted in Claveria, Misamis Oriental, Mindanao, Philippines through interviews with 192 farmers, 86% of whom practiced tree-based farming systems and the rest cash cropping, corn being the dominant crop. Tobit regression analysis was used to analyze the factors influencing farmers’ investment decision in tree-based systems. Results revealed that a high relative price variability (timber price vis-a-vis cash crop prices) deters tree planting. Farmers tree-growing decisions also depend on (1) current price levels and forecast price changes, (2)socio-economic characteristic such as household size, age, and education, (3) farm characteristics given by cultivable land-man ratio, and farm size, (4) land tenure, (5) knowledge about tree-based land-use systems, (6) membership in landcare association. The study recommends that since price risk appears to be the major deterrent to expansion of tree farming, measures to reduce said risk or to improve risk management capability of farmers be adopted, including (a) provision of relevant and timely price information and (b) price risk insurance. The long-term nature of the investment in trees requires security of land tenure as confirmed by the adoption model. There is a need to continue the information dissemination activities through farmers’ trainings and seminars. Finally, the influence of a landcare association on farmers’ decision to adopt tree-based land-use systems implies the need of this local initiative to be further enhanced and developed.
Keywords: Farmers groups; Smallholder farmers; Technology adoption patterns; Tree farming